Integrable Sys Quantum Field Theory 1989
DOI: 10.1016/b978-0-12-385342-4.50007-x
|View full text |Cite
|
Sign up to set email alerts
|

Eigenvalue Spectrum of the Superintegrable Chiral Potts Model

Abstract: We compute the eigenvalues of the 3-state superintegrable chiral Potts model and of the associated spin chain by use of a functional equation. We find that the system has four phases, two of which are massless and two of which are massive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
251
0

Year Published

1989
1989
2008
2008

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(258 citation statements)
references
References 20 publications
7
251
0
Order By: Relevance
“…(2.26) 1 The identity (2.24) is formula (2.44) in [17] where rapidities are in (2.8). The same equality holds also in the degenerate model with rapidities in (2.9).…”
Section: The Chiral Potts Model and The Degenerate Selfdual Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…(2.26) 1 The identity (2.24) is formula (2.44) in [17] where rapidities are in (2.8). The same equality holds also in the degenerate model with rapidities in (2.9).…”
Section: The Chiral Potts Model and The Degenerate Selfdual Modelmentioning
confidence: 99%
“…Furthermore, the Q-operator investigation of the five-parameter τ (2) -family appearing in [19] has shown that the τ (2) -model is indeed the same theory as the chiral Potts model of alternating rapidities when the degenerate forms are included [41]. This suggests the results in [1,11,12,10,31] about the eigenvalue spectrum could be better understood through a general setting of the chiral Potts model with alternating rapidities, including the degenerate cases. Indeed, after sorting out the technical details, one finds the functional relations in [17] about the chiral Potts model with alternating rapidities also valid in the degenerate cases (for the details, see [41]).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This indicate that a non perturbative definition of the vacuum must be given and is often a signal that level crossing of the vacuum has occurred [32]. Similarly for the φ 2,1 perturbation they find a problem with vacuum definition for 3p > 2p ′ .…”
Section: Introductionmentioning
confidence: 97%